The Level of Persistence in Completing Tasks Based on the Student's Potential - Safari Safari; Khasanah Khasanah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The main objective of this study is to determine whether there is a relationship between the level of persistence in completing assignments and students' potential. The design used in this study is quantitative research. This study utilized data from the AKM 2020 SMA / SMK examination results held by Pusmenjar. This study's population is the satisfaction level of SMA / SMK students studying with teachers at school in 2020, while the sample is the degree of satisfaction of SMA / SMK students taking the 2020 AKM exam. SMA / SMK participants of AKM 2020 (514 districts/districts in 34 provinces in Indonesia). Based on the results of simple regression and part analysis, the following results were obtained. Even though the contribution is not particularly large—0.14% to be exact—statistically speaking, there is a positive relationship between the level of tenacity in finishing activities and one's self-potential (P 0.05). The health of students in understanding the material is most influenced by (1) feelings of nervousness or anxiety (-0.015), (2) getting carried away or easily angry (-0.016), (3) insomnia (-0.018), and deep feelings of sadness. Or depressed (-0.094). The contribution of the four variables (anxiety, anger, insomnia, and sadness) to students' health is relatively high, 0.605 (61%), while other variables influence the remaining 39%. The relationship between student health and subject matter is 0.286 (29%). The findings lead us to conclude that there is a statistically significant correlation (P 0.05) between the degree of students' self-potential and the amount of effort they put into finishing their tasks.